Risk of dietary exposure to aflatoxins and fumonisins in infants less than 6 months of age in Rombo, Northern Tanzania. Issue 3 (24th November 2014) - Magoha, Happy; Kimanya, Martin; De Meulenaer, Bruno; Roberfroid, Dominique; Lachat, Carl; Kolsteren, Patrick
Abstract: Infants less than 6 months of age receiving foods other than breast milk are at a high risk of exposure to mycotoxins. We surveyed food intake and estimated the risk of exposures to aflatoxin and fumonisin mycotoxins for infants less than 6 months of age in Northern Tanzania. A total of 143 infants were progressively recruited and three follow‐up visits were made at 1, 3 and 5 months of age. A 24‐h dietary recall technique was used to estimate flour intake of infants who had been introduced to maize foods. Aflatoxins and fumonisins in the flours were analysed using high‐performance liquid chromatography technique. Exposure to aflatoxins or fumonisins was estimated using the deterministic approach. By the age of 3 months, 98 infants had started taking food; 67 of them, maize flours at levels ranging from 0.57 to 37.50 g per infant per day (average 8 g per infant per day). Fifty‐eight per cent of 67 maize flour samples contained detectable aflatoxins (range 0.33–69.47 μ g kg −1 ; median 6 μ g kg −1 ) and 31% contained detectable fumonisins (range 48–1224 μ g kg −1 ; median 124 μ g kg −1 ). For infants who consumed contaminated flours, aflatoxin exposure ranged from 0.14 to 120 ng kg −1 body weight (BW) per day (all above the health concern level of 0.017 ng kg −1 BW per day as recommended by the European Food Safety Agency) and fumonisin exposure ranged from 0.005 to 0.88 μ g kg −1 BW per day. Insignificant association was observed between exposure to fumonisins or aflatoxins and stunting or underweight. Reducing aflatoxin and fumonisin contamination of maize and dietary diversification can prevent infants and the public, in general, from exposure to the toxins.